Leaf insects from Luzon, Philippines, with descriptions of four new species, the new genus Pseudomicrophyllium, and redescription of Phyllium (Phyllium) geryon Gray, 1843, (Phasmida: Phylliidae) - Cumming, Royce T.; Leong, Jing V.; Lohman, David J. (Zootaxa, 2017)
Examination of unidentified Phylliidae specimens revealed a number of undescribed species from the island of Luzon, Philippines. Morphological and molecular study of specimens from the obscure phasmid genus Microphyllium Zompro, 2001, revealed a new species, which we describe as Microphyllium haskelli Cumming sp. nov.. It is here described and differentiated from the two other species in the genus, both currently only known from adults of a single sex. Pseudomicrophyllium Cumming gen. nov. is described as a new genus within Phylliidae with the type species Pseudomicrophyllium faulkneri Cumming gen. et sp. nov. as the sole known species in the genus. As is unfortunately often the case in the leaf-mimicking family Phylliidae, this new genus and species is only known from a single specimen. In addition to the new genus, two new Phyllium (Phyllium) species from the siccifolium species-group are named and described as Ph. (Ph.) antonkozlovi Cumming sp. nov. and Ph. (Ph.) bourquei Cumming & Le Tirant sp. nov.. In addition to the newly described species, Phyllium (Phyllium) geryon Gray, 1843 is redescribed from a nearly perfect specimen, completing some of the morphological knowledge gaps currently missing because of the severely damaged holotype specimen. A key to all known species of Phylliidae from Luzon is included. Holotype specimens for all four new species will be deposited in the National Museum of the Philippines type collection and paratype specimens will be deposited into the San Diego Natural History Museum collection or retained within the first author’s collection.